2020
DOI: 10.1016/j.isci.2020.100838
|View full text |Cite
|
Sign up to set email alerts
|

DNMT3B Oncogenic Activity in Human Intestinal Cancer Is Not Linked to CIMP or BRAFV600E Mutation

Abstract: Approximately 10% of human colorectal cancer (CRC) are associated with activated BRAFV600E mutation, typically in absence of APC mutation and often associated with a CpG island methylator (CIMP) phenotype. To protect from cancer, normal intestinal epithelial cells respond to oncogenic BRAFV600E by activation of intrinsic p53 and p16-dependent tumor suppressor mechanisms, such as cellular senescence. Conversely, CIMP is thought to contribute to bypass of these tumor suppressor mechanisms, e.g. via epigenetic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…MacKenzie et al revealed that DNMT3b was frequently amplified and overexpressed in CRC. 28 DNMT3b was upregulated in endometrial cancer samples from patients, and promoted endometrial cancer cell proliferation, as evidenced by assays of cell viability, cell cycle, colony formation. 29 Camero et al provided that DNMT3b depletion induced significant DNA damage and impaired the DNA repair machinery in rhabdomyosarcoma.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…MacKenzie et al revealed that DNMT3b was frequently amplified and overexpressed in CRC. 28 DNMT3b was upregulated in endometrial cancer samples from patients, and promoted endometrial cancer cell proliferation, as evidenced by assays of cell viability, cell cycle, colony formation. 29 Camero et al provided that DNMT3b depletion induced significant DNA damage and impaired the DNA repair machinery in rhabdomyosarcoma.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we found only DNMT3b showed significant overexpression in both patients with COAD and READ and CRC cells among three DNMTs. MacKenzie et al revealed that DNMT3b was frequently amplified and overexpressed in CRC 28 . DNMT3b was upregulated in endometrial cancer samples from patients, and promoted endometrial cancer cell proliferation, as evidenced by assays of cell viability, cell cycle, colony formation 29 .…”
Section: Discussionmentioning
confidence: 99%
“…As a component in the newly identified PHF14/DNMT3B complex, DNMT3B is known as one of the two de novo DNA methyltransferases responsible for generating 5-methylcytosine by transferring the methyl-group from S-adenosyl methionine to the fifth carbon of unmethylated cytosine 47 . Previous studies have found that DNMT3B could be upregulated by TGF-β signaling activation 45 , and that DNMT3B overexpression accelerates malignant transformation, promotes cancer progression and induces drug resistance in liver cancer, colon cancer and breast cancer, through enhancing DNA hypermethylationmediated epigenetic suppression of tumor suppressor genes 18,19,[48][49][50] . Interestingly, DNMT3A, a paralogue of DNMT3B, predominantly plays a tumor-suppressive role in cancers 51 .…”
Section: Discussionmentioning
confidence: 99%